Feedback control strategy for optimizing biohydrogen production from organic solid waste in a discontinuous process. (19th October 2021) - Jiménez-Ocampo, Ulises E.; Santiago, Sonia G.; Vargas, Alejandro; Moreno-Andrade, Iván
Abstract: The use of control strategies for the biological process of hydrogen (H2 ) production can increase productivity, stability, and robustness, increasing the viability of the implementation of these systems at the industrial level. A feedback control strategy for optimizing biohydrogen production from organic solid waste in a discontinuous process was proposed and pragmatically tested. The control strategy, which is based on recursively fitting a modified Gompertz model to gathered online data of the cumulative H2 volume, could eventually stabilize the system at an optimal reaction time. The control strategy was evaluated during 140 degradation cycles maintaining a stable H2 production with a reproducible form in the cumulative H2 production curve. Independent of the changes in the microbial population dynamics in the reactor, the control strategy maintained a stable H2 production avoiding the presence of methanogenic archaea. With the proposed controller, a compromise between the needed HRT and the H2 production was obtained. Highlights: A feedback control strategy for H2 production was proposed and validated. The control maintained stable and reproducible bioH2 production. A compromise between the needed HRT and the bioH2 production was obtained.